2001
DOI: 10.1046/j.0022-202x.2001.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Interleukin-10 Therapy on Psoriatic Skin Lesions: Histologic, Immunohistologic, and Molecular Biology Findings

Abstract: Interleukin-10 is an important anti-inflammatory and immunosuppressive cytokine with major impact on several immune reactions, including regulatory mechanisms in the skin. Recently, we performed a phase II trial in psoriatic patients receiving subcutaneously interleukin-10 over 7 wk. The clinical response suggested that interleukin-10 might represent a novel anti-psoriatic drug. In order to understand better the mode of action and to elucidate the effects of systemic interleukin-10 treatment on the skin immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 32 publications
2
38
2
3
Order By: Relevance
“…Exemplary, the CXCR2 ligand CXCL8 (IL-8), as a major neutrophilrecruiting and -activating factor, is found to be diminished in vitro also without prior stimulation by LPS and can be confirmed also in vivo (Table 1) [19].…”
Section: Chemokinesmentioning
confidence: 94%
“…Exemplary, the CXCR2 ligand CXCL8 (IL-8), as a major neutrophilrecruiting and -activating factor, is found to be diminished in vitro also without prior stimulation by LPS and can be confirmed also in vivo (Table 1) [19].…”
Section: Chemokinesmentioning
confidence: 94%
“…It inhibits a broad array of inflammatory processes such as T helper Type I cell (proinflammatory) cytokine production, antigen presentation and antigen-specific T cell proliferation [20,21]. It is demonstrated that IL-10 decreases inflammatory activity in vivo, as shown in T helper Type I mediated diseases such as psoriasis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological significance of these findings was reflected by the depressed DTH reaction to recall antigens during IL-10 therapy (Asadullah et al, 1999a). Interestingly, IL-10 therapy led to a decrease in cutaneous IL-8 and an increase in IL-4 expression, both of which might contribute to the antipsoriatic effect (Asadullah et al, 2001b;Reich et al, 2001). Direct effects of IL-10 on keratinocytes are unlikely to have contributed to the clinical response, since the IL-10 unresponsiveness of keratinocytes has been demonstrated by us recently (see above).…”
Section: Friedrich Et Al 2002mentioning
confidence: 99%